Reforms protecting minority shareholders and firm performance: International evidence - Corina Burunciuc; Halit Gonenc (Journal of Risk and Financial Management, 2021)
This study investigates the effect of corporate governance reforms protecting minority shareholders on the firm value measured by Tobin's Q. Using the difference-in-differences estimation and a large international sample from 65 countries for the period 2005-2018, the results show that the firm values increase more in the reform countries than non-reform countries relative to pre-reform levels. This positive effect changes for firms with high and low levels of debt. Moreover, the values after reforms increase more for firms located in civil countries and in countries with rule-based reform approaches and low debt enforcement because the reforms strengthening minority shareholder protection are more efficient in those countries. The evidence is robust to accounting-based performance as well.
Keywords: 330; reforms protecting minority shareholders; firm value; corporate governance; leverage; legal origin; corporate governance approaches; debt enforcement